Investigating the environmental interpretation of oxygen and carbon isotope data from whole and fragmented bivalve shells - Lacey, J.H.; Leng, M.J.; Peckover, E.N.; Dean, J.R.; Wilke, T.; Francke, A.; Zhang, X.; Masi, A.; Wagner, B. (Elsevier, 2018)
Sclerochronological data from whole bivalve shells have been used extensively to derive palaeoenvironmental information. However, little is known about the relevance of shell fragments more commonly preserved in the sediment record. Here, we investigate the oxygen and carbon isotope composition of Dreissena carinata fragments from a core recovered from Lake Dojran (FYRO Macedonia/Greece) to identify their relevance and efficacy as a proxy in palaeoenvironmental studies. We use a modern Dreissena shell to calibrate the relationship between the bivalve and its contemporary environment, which suggests their isotope composition is primarily a function of temperature and water balance. The range of fragment isotope data from the core overlaps with that of unbroken fossil shells, suggesting the fragments broadly record lakewater conditions across the time of deposition. A comparison of the isotope composition of shell fragments and endogenic carbonate shows an offset between the two sets of data, which is likely due to temperature differences between surface and bottom waters, the timing of carbonate precipitation, and productivity-controlled stratification of the dissolved inorganic carbon pool. Shell fragment isotope data seem to reflect the signal of environmental change recorded in other proxy data from the same core and may potentially be used (like endogenic carbonate) to provide information on past changes in lake level.